The Effectiveness of Ketamine in Pediatric Acute Deafferentation Pain after Spinal Cord Injury - Devina G. Shiwlochan; Misty Shah; Khushboo Baldev; Donna-Ann Thomas; Maxime Debrosse (Case Reports in Anesthesiology)
Deafferentation pain and allodynia commonly occur after spinal cord trauma, but its treatment is often challenging. The literature on effective therapies for pediatric deafferentation pain, especially in the setting of spinal cord injury, is scarce. We report the case of a 12-year-old patient with acute allodynia after a gunshot injury to the spine. The pain was refractory to multiple analgesics, but resolved with ketamine, which also improved the patient’s physical function and quality of life, a trend that continued many months after the injury. We suggest that early initiation of ketamine may be effective for acute pediatric deafferentation pain secondary to spinal cord injury, as well as preventing chronic pain states in that population.